Monitorization of the effects of spinal anaesthesia on cerebral oxygen saturation in elder patients using near-infrared spectroscopy - Kusku,Aysegul (2014)
OBJECTIVE: Central blockage provided by spinal anaesthesia enables realization of many surgical procedures, whereas hemodynamic and respiratory changes influence systemic oxygen delivery leading to the potential development of series of problems such as cerebral ischemia, myocardial infarction and acute renal failure. This study was intended to detect potentially adverse effects of hemodynamic and respiratory changes on systemic oxygen delivery using cerebral oxymetric methods in patients who underwent spinal anaesthesia. METHODS: Twenty-five ASA I-II Group patients aged 65-80 years scheduled for unilateral inguinal hernia repair under spinal anaesthesia were included in the study. Following standard monitorization baseline cerebral oxygen levels were measured using cerebral oximetric methods. Standardized Mini Mental Test (SMMT) was applied before and after the operation so as to determine the level of cognitive functioning of the cases. Using a standard technique and equal amounts of a local anaesthetic drug (15 mg bupivacaine 5%) intratechal blockade was performed. Mean blood pressure (MBP), maximum heart rate (MHR), peripheral oxygen saturation (SpO2) and cerebral oxygen levels (rSO2) were preoperatively monitored for 60 min. Pre- and postoperative haemoglobin levels were measured. The variations in data obtained and their correlations with the cerebral oxygen levels were investigated. RESULTS: Significant changes in pre- and postoperative measurements of haemoglobin levels and SMMT scores and intraoperative SpO2 levels were not observed. However, significant variations were observed in intraoperative MBP, MHR and rSO2 levels. Besides, a correlation between variations in rSO2, MBP and MHR was determined. CONCLUSION: Evaluation of the data obtained in the study demonstrated that post-spinal decline in blood pressure and also heart rate decreases systemic oxygen delivery and adversely effects cerebral oxygen levels. However, this downward change did not result in deterioration of cognitive functioning.